2017
DOI: 10.1017/s002193201700044x
|View full text |Cite
|
Sign up to set email alerts
|

Fragile Environment, Seasonality and Maternal and Childhood Undernutrition in Bangladesh

Abstract: Summary. This study assessed whether agricultural and household incomes were the same across different agro-ecological environments in Bangladesh. An in-depth analysis of the effect of unfavourable ecologies on maternal and child malnutrition was carried out. Data were from a longitudinal data set comprising a nationally representative data sample collected in 2014 and the Food Security Nutrition Surveillance Project (FSNSP) conducted in 2011 and 2012. Anthropometric indices were used to assess the nutritional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Our study suggested seasonal household food insecurity as an independent predictor of decreased WHZ (Table 5), which is in accordance with previous investigations 57, 58 . This could be attributable to seasonal fluctuations in household food consumption patterns 11, 59 , and some scholars describe seasonality as a grossly neglected dimension of poverty 11, 17, 60 .…”
Section: Discussionsupporting
confidence: 93%
“…Our study suggested seasonal household food insecurity as an independent predictor of decreased WHZ (Table 5), which is in accordance with previous investigations 57, 58 . This could be attributable to seasonal fluctuations in household food consumption patterns 11, 59 , and some scholars describe seasonality as a grossly neglected dimension of poverty 11, 17, 60 .…”
Section: Discussionsupporting
confidence: 93%
“…Even with the rapid social changes and economic development, the distribution of wealth is unequal within the population. This inequality explains the sizable proportion of undernourished women in this rural community and other parts of the country [ 31 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…56 Our study suggested seasonal HFI as an independent predictor of decreased WHZ (table 5), which is in accordance with previous investigations. 57 58 This could be attributable to seasonal fluctuations in household food consumption patterns, 11 59 and some scholars describe seasonality as a grossly neglected dimension of poverty. 11 17 60 Meanings and possible explanations Seasonal HFI could contribute to decreased WHZ indices in rural Ethiopia, suggesting that this population is vulnerable to food insecurity.…”
Section: Open Accessmentioning
confidence: 99%